PROSES DEKANTASI MINYAK ATSIRI DENGAN VARIASI PLAT INTERCEPTOR DALAM DEKANTER - Rajendra, I M.; Anom Arsani, I. A. (Jurnal Kimia (Journal of Chemistry); Vol. 3, No. 2 Juli 2009)
Decantation process was done to separate oil and water. Mostly, Small Medium Enterprises (SME) use low traditional technology as multiple drums. As a result, there is much oil dumped together with wastewater. A better way to decant oil and water can be done by using an interceptor plate in decanter equipment. This research aims was to test the performance of decanter with special design by using an interceptor plate. The observation focused on distance between plates toward the oil content in wastewater, which was measured by its density. Three variables of plate distance were 10 mm, 20 mm, and 30 mm. Material tests were nilam and clove oil with several concentrations i.e. 1.96%, 3.85% and 5.66%, and the flow rate was adjusted at 2 liters/minute. The result shown that the interceptor plate with 10mm distance produced wastewater with lower content of oil. In addition, in industry scale test, the decanter having 10mm distance plate interceptor could reduce oil loss up to 11.8% for nilam and 42.9% for clove compared to that of multiple drum.
Keywords: Interceptor plate, decantation, essential oil